Isolating Effects of Temperature and Light on Nutrient Acquisition by Biofilm and Bryophyte Communities in Arctic Spring-Stream Ecosystems - Tori A. Hebert; Adam C. Hensley; Carla L. Atkinson; Jonathan P. Benstead; Alexander D. Huryn (Ecosystems, 2026)

Phylogenomic analyses reveal introgression and cryptic speciation in the globally distributed, vector-transmitted pathogen Plasmodium relictum - Esther Weyer; Angela N. Theodosopoulos; Vaidas Palinauskas; Staffan Bensch; Helena Westerdahl; Mélanie Duc; Arif Ciloglu; Xi Huang; Kyeong Soon Kim; Yoshio Tsuda; Carter T. Atkinson; Pavel Zehtindjiev; et al. (Molecular Phylogenetics and Evolution, 2026)

Comparative Effects of Thermal Recovery Strategies on Strength, Muscle Soreness and Molecular Markers Following Exercise-Induced Muscle Damage in Healthy Adults - F. Bayne; M. Nagyova; N. Stolk; M.A. Placido; M. Hamdi; A. Falzon; R. Perezen; S. Neto Menezes; S. Haliti; C. Atkinson; S. Racinais; N. Gaoua (Journal of Thermal Biology, 2026)

Relative accuracy of point-of-care tests to rule-in heartworm infection in clinically suspected dogs using Bayesian latent class modelling - P.J. Atkinson; C. Quimby; A. Datt; T.D. Nielsen; C.G.B. Caraguel (Preventive Veterinary Medicine, 2026)

Contemporary Methods for Capturing Juvenile Salmonids in the Marine Environment - Sean C. Godwin; Emma M. Atkinson; Jamieson B. Atkinson; Mackenzie C. Bartlett; William D. P. Duguid; Marc Trudel; Andrew W. Bateman (Fish and Fisheries, 2026)
Anadromous salmonids play vital roles in marine and freshwater ecosystems. The most abundant of these fishes—Pacific salmon ( Oncorhynchus spp.)—are integral to coastal ecosystems and communities across the North Pacific Rim, but numerous populations are experiencing dramatic declines, particularly towards the south of their range. Although many declines have been linked to poor marine survival, the early marine life phase of salmon has historically been difficult to study because of challenges in capturing juvenile salmon once they leave freshwater. Recent advancements in capture methods, refined over decades of research, have greatly expanded our understanding of juvenile Pacific salmon life history. Here, we synthesise and review the literature on the five main capture techniques for juvenile Pacific salmon in the marine environment: beach seine, miniature purse seine, conventional purse seine, microtroll, and rope trawl. We compare gear, selectivity, cost, and fish welfare considerations across methods. Along with demonstrated utility in Pacific salmon research, these methods also have broad—and in some cases unexplored—applicability for studying other salmonids and nearshore marine fishes globally, including invasive populations and Atlantic salmon.

Genomic Architecture of Inbreeding Depression Associated With Hatching Failure in an Endangered Parrot - Yasmin Foster; Stefanie Grosser; Brodie J. Foster; Nicolas Dussex; Aimee Stubbs; Ludovic Dutoit; Theo Atkinson; Fiona Robertson; Ken G. Dodds; Rudiger Brauning; Jeanne M. E. Jacobs; John C. McEwan; et al. (Molecular Ecology, 2026)
Conservation management of endangered species increasingly relies on genomic approaches to understand how long‐term small population sizes affect the fitness of extant individuals. However, despite the growing investment in genomic resources by conservation programmes, the impact that sequencing methods have on the ability to detect inbreeding‐related phenomena has been largely overlooked. Here, we compare the use of whole‐genome and reduced‐representation sequencing approaches in 148 individuals of the critically endangered parrot, the kākāpō ( Strigops habroptilus ), to assess inbreeding and its effects on female reproductive success. We explore how sequencing choice influences the identification of long stretches of homozygosity across the genome (runs of homozygosity, ROH), and compare the conservation implications of the results produced by each method. Both whole‐genome and reduced‐representation sequencing approaches provided comparable estimates of genome‐wide inbreeding ( F ROH ) and revealed consistent effects on egg hatching success, suggesting that reduced‐representation sequencing is capable of detecting inbreeding depression in wild populations under certain conditions. Whole‐genome sequencing enabled chromosome‐level inbreeding analyses, which revealed no strong evidence of chromosome‐specific effects beyond the genome‐wide signal. These results suggest that inbreeding depression in kākāpō reflects small effects across many chromosomes rather than strong effects on only a few, and that the primary benefit of whole‐genome sequencing lies in improving the precision of genome‐wide inbreeding estimates rather than identifying chromosome‐specific effects. Our findings highlight the distinct benefits of each sequencing approach in conservation, particularly within the context of resource limitations.

Environmental gradients drive convergence in life history strategies among disparate but coevolved taxonomic groups - Carla L. Atkinson; Alex J. Franzen; Garrett W. Hopper; Jonathan W. Lopez; Zachery D. Zbinden; Caryn C. Vaughn (Ecology, 2025)
Trait‐based approaches can improve ecological understanding by linking fitness to the environment. The trilateral life history model is an expansion of r‐ and K‐selection theory that reflects trade‐offs between juvenile survival, fecundity, and generation time and describes differential survival of species across environmental gradients. We used this framework to generate and test hypotheses regarding community assembly and the validity of such a model in two disparate taxonomic groups, freshwater mussels and fish. We assessed the distribution of mussel and fish life history strategies across 80 sites spanning aspects of the river continuum concept within the Ouachita Highlands (USA) and asked if their distributions are predicted by a similar life history strategy framework. Because mussel and fish assemblages should both be structured by selective forces in an up‐ to downstream trajectory, we expected both taxa to converge on more species‐rich assemblages with a greater proportion of equilibrium strategists in larger, more stable downstream habitats. We found that both mussel and fish species richness increased with watershed area as well as the proportion of equilibrium strategists in the assemblages. Our study validates the use of the trilateral life history model to test hypotheses about the distribution patterns of two coevolved taxonomic groups.

Establishing a basis for recognising marine ‘other effective area-based conservation measures’ (OECMs) in South Africa - SP Kirkman; P Kowalski; SD Holness; LJ Atkinson; R Brand; L Dunga; TP Fairweather; T Goldman; D Marnewick; J Nhleko; R Peter; C Smith; et al. (African Journal of Marine Science, 2025)

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

A role for dendroecology in guiding hydrologic restoration and mitigating risks of peatland soil loss: an example from Chamaecyparis thyoides forests - Robert B. Atkinson; Abigail Weaver; Joshua A. Kincaid; Frederic C. Wurster; James M. B. Doyle (Trees, 2025)
Key message Tree rings of Chamaecyparis thyoides exhibit growth responses that are influenced by local hydrologic conditions through decadal timescales. That perspective can assist peatland natural resource managers in selection of hydrologic restoration targets that minimize chronic microbial oxidation and acute peat loss associated with fire. Abstract Temperate forested peatlands are valued for myriad ecosystem services including carbon storage and biodiversity which may be lost through anthropogenic disturbance of hydrologic regimes. Hydrologic alterations may be recorded in tree stem growth patterns and provide insights for management and restoration. In Chamaecyparis thyoides (Atlantic White Cedar, Juniper) swamps, stand drainage causes a shift from net soil carbon sink to source as microbial oxidation and catastrophic fire oxidize stored organic matter. Here, we analyze historic radial growth patterns in C. thyoides in order to characterize drainage history to guide hydrologic management for peat conservation and restoration. Basal area increment (BAI) estimates across a ~ 60-year chronology (1939–2003) were analyzed by flexible beta cluster analysis of 185 trees from 13 C. thyoides stands in the Great Dismal Swamp National Wildlife Refuge in Virginia and North Carolina, USA. Stands formed 3 groups, and growth rates among all groups were indicative of a drained hydrologic regime throughout the chronology compared to an undrained control stand. Regime shift analyses identified positive shifts for 2 stand groups in 1954 and for all 3 stand groups in 1963. Multiple response permutation procedures and partial mantel tests both identified two predictive growth variables including (1) visual observations of fluctuation in the water table and (2) proximity to a primary ditch. Growth rate was suppressed when weirs were installed in the mid-1980s; however, growth rebounded within ~ 2 years. The chronology ends when stands were struck by a major hurricane in 2003 and fires in 2008 and 2011 liberated 1.38 Tg of peat carbon. We conclude that dendroecology can detect hydrologic changes through time and can reduce risks of microbial oxidation and catastrophic fire in forested peatlands.

Pace of alcohol drinking during in natural-environment drinking is associated with heightened alcohol-related reward and negative consequences in risky drinkers - Emily A. Atkinson; Andrew M. Fischer; John F. Cursio; Andrea C. King; Daniel J. Fridberg (Psychopharmacology, 2025)

Causes and consequences of long-term defaunation in multi-species aggregations: species traits predict freshwater mussel declines and decreases in biogeochemical storage and recycling - Jonathan W. Lopez; Carla L. Atkinson; Caryn C. Vaughn (Oecologia, 2025)

Integration of genetic, taxonomic, and functional dimensions of biodiversity yields conservation insights - Carla L. Atkinson; Irene Sánchez González; Jamie R. Bucholz; Garrett W. Hopper; Ryan C. Garrick; Colin R. Jackson; Jeffrey D. Lozier (Biological Conservation, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Shorebirds Are Shrinking and Shape‐Shifting: Declining Body Size and Lengthening Bills in the Past Half‐Century - A. McQueen; M. Klaassen; G. J. Tattersall; S. Ryding; R. Atkinson; R. Jessop; C. J. Hassell; M. Christie; A. Fröhlich; M. R. E. Symonds (Ecology Letters, 2024)
Animals are predicted to shrink and shape‐shift as the climate warms, declining in size, while their appendages lengthen. Determining which types of species are undergoing these morphological changes, and why, is critical to understanding species responses to global change, including potential adaptation to climate warming. We examine body size and bill length changes in 25 shorebird species using extensive field data (> 200,000 observations) collected over 46 years (1975–2021) by community scientists. We show widespread body size declines over time, and after short‐term exposure to warmer summers. Meanwhile, shorebird bills are lengthening over time but shorten after hot summers. Shrinking and shape‐shifting patterns are consistent across ecologically diverse shorebirds from tropical and temperate Australia, are more pronounced in smaller species and vary according to migration behaviour. These widespread morphological changes could be explained by multiple drivers, including adaptive and maladaptive responses to nutritional stress, or by thermal adaptation to climate warming.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

New insights into pesticide occurrence and multicompartmental monitoring strategies in stream ecosystems using periphyton and suspended sediment - Moira M. Ijzerman; Melanie Raby; Nicholas V. Letwin; Yaryna M. Kudla; Jenna D. Anderson; Brian J. Atkinson; Rebecca C. Rooney; Paul K. Sibley; Ryan S. Prosser (Science of The Total Environment, 2024)

The relationship between central Indian terrestrial vegetation and monsoon rainfall distributions in different hydroclimatic extreme years using time-series satellite data - B. Singh; C. Jeganathan; V.S. Rathore; P.M. Atkinson; M.D. Behera; C.P. Singh; J. Dash; P.S. Roy (Theoretical and Applied Climatology, 2024)

Assessment of major ions in groundwater supplied to Monterrey metropolitan area, Mexico: quality assurance, technical analysis, and addenda - J. C. Atkinson (International Journal of Environmental Science and Technology, 2024)

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Community‐wide correlations between species richness, abundance and population genomic diversity in a freshwater biodiversity hotspot - Jamie R. Bucholz; Garrett W. Hopper; Irene Sánchez González; Taylor E. Kelley; Colin R. Jackson; Ryan C. Garrick; Carla L. Atkinson; Jeffrey D. Lozier (Molecular Ecology, 2023)
Understanding patterns of diversity across macro (e.g. species‐level) and micro (e.g. molecular‐level) scales can shed light on community function and stability by elucidating the abiotic and biotic drivers of diversity within ecological communities. We examined the relationships among taxonomic and genetic metrics of diversity in freshwater mussels (Bivalvia: Unionidae), an ecologically important and species‐rich group in the southeastern United States. Using quantitative community surveys and reduced‐representation genome sequencing across 22 sites in seven rivers and two river basins, we surveyed 68 mussel species and sequenced 23 of these species to characterize intrapopulation genetic variation. We tested for the presence of species diversity–abundance correlations (i.e. the more‐individuals hypothesis, MIH), species‐genetic diversity correlations (SGDCs) and abundance‐genetic diversity correlations (AGDCs) across all sites to evaluate relationships between different metrics of diversity. Sites with greater cumulative multispecies density (a standardized metric of abundance) had a greater number of species, consistent with the MIH hypothesis. Intrapopulation genetic diversity was strongly associated with the density of most species, indicating the presence of AGDCs. However, there was no consistent evidence for SGDCs. Although sites with greater overall densities of mussels had greater species richness, sites with higher genetic diversity did not always exhibit positive correlations with species richness, suggesting that there are spatial and evolutionary scales at which the processes influencing community‐level diversity and intraspecific diversity differ. Our work reveals the importance of local abundance as indicator (and possibly a driver) of intrapopulation genetic diversity.

Landscape fires disproportionally affect high conservation value temperate peatlands, meadows, and deciduous forests, but only under low moisture conditions - Máire Kirkland; Philip W. Atkinson; James W. Pearce-Higgins; Mark C. de Jong; Thomas P.F. Dowling; Dmitri Grummo; Megan Critchley; Adham Ashton-Butt (Science of The Total Environment, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Pathways to achieving nature-positive and carbon–neutral land use and food systems in Wales - Sarah M. Jones; Alison C. Smith; Nicholas Leach; Peter Henrys; Peter M. Atkinson; Paula A. Harrison (Regional Environmental Change, 2023)
Land use and its management can play a vital role in carbon sequestration, but trade-offs may exist with other objectives including food security and nature recovery. Using an integrated model (the FABLE calculator), four pathways, co-created with colleagues at the Welsh Government, towards achieving climate and biodiversity targets in Wales were explored: status quo, improvements on current trends, land sparing and land sharing. We found that continuing as usual will not be sufficient to meet Wales’s climate and biodiversity targets. In contrast, the land use and agricultural sector became a net carbon sink in both the land sparing and land sharing pathways, through high afforestation targets, peatland restoration, reducing food waste and moving towards a healthier diet. Whilst both pathways released land for biodiversity, the gains were greater in the land sharing pathway, which was also less dependent on optimistic assumptions concerning productivity improvements. The results demonstrate that alternative approaches to achieving nature-positive and carbon–neutral land use and food systems may be possible, but they come with stringent and transformative requirements for policy changes, with an integrated approach necessary to maximise benefits for climate, food and nature.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

The Role of Satellite Telemetry Data in 21st Century Conservation of Polar Bears (Ursus maritimus) - Kristin L. Laidre; George M. Durner; Nicholas J. Lunn; Eric V. Regehr; Todd C. Atwood; Karyn D. Rode; Jon Aars; Heli Routti; Øystein Wiig; Markus Dyck; Evan S. Richardson; Stephen Atkinson; et al. (Frontiers in Marine Science, 2022)
Satellite telemetry (ST) has played a critical role in the management and conservation of polar bears ( Ursus maritimus ) over the last 50 years. ST data provide biological information relevant to subpopulation delineation, movements, habitat use, maternal denning, health, human-bear interactions, and accurate estimates of vital rates and abundance. Given that polar bears are distributed at low densities over vast and remote habitats, much of the information provided by ST data cannot be collected by other means. Obtaining ST data for polar bears requires chemical immobilization and application of a tracking device. Although immobilization has not been found to have negative effects beyond a several-day reduction in activity, over the last few decades opposition to immobilization and deployment of satellite-linked radio collars has resulted in a lack of current ST data in many of the 19 recognized polar bear subpopulations. Here, we review the uses of ST data for polar bears and evaluate its role in addressing 21 st century conservation and management challenges, which include estimation of sustainable harvest rates, understanding the impacts of climate warming, delineating critical habitat, and assessing potential anthropogenic impacts from tourism, resource development and extraction. We found that in subpopulations where ST data have been consistently collected, information was available to estimate vital rates and subpopulation density, document the effects of sea-ice loss, and inform management related to subsistence harvest and regulatory requirements. In contrast, a lack of ST data in some subpopulations resulted in increased bias and uncertainty in ecological and demographic parameters, which has a range of negative consequences. As sea-ice loss due to climate warming continues, there is a greater need to monitor polar bear distribution, habitat use, abundance, and subpopulation connectivity. We conclude that continued collection of ST data will be critically important for polar bear management and conservation in the 21 st century and that the benefits of immobilizing small numbers of individual polar bears in order to deploy ST devices significantly outweigh the risks.

Biotic factors limit the invasion of the plague pathogen ( Yersinia pestis ) in novel geographical settings - Henry G. Fell; Owen G. Osborne; Matthew D. Jones; Steve Atkinson; Simon Tarr; Suzanne H. Keddie; Adam C. Algar (Global Ecology and Biogeography, 2022)
Aim The distribution of Yersinia pestis , the pathogen that causes plague in humans, is reliant upon transmission between host species; however, the degree to which host species distributions dictate the distribution of Y. pestis , compared with limitations imposed by the environmental niche of Y. pestis per se, is debated. We test whether the present‐day environmental niche of Y. pestis differs between its native range and an invaded range and whether biotic factors (host distributions) can explain observed discrepancies. Location North America and Central Asia. Major taxa studied Yersinia pestis . Methods We use environmental niche models to determine whether the current climatic niche of Y. pestis differs between its native range in Asia and its invaded range in North America. We then test whether the inclusion of information on the distribution of host species improves the ability of models to capture the North American niche. We use geographical null models to guard against spurious correlations arising from spatially autocorrelated occurrence points. Results The current climatic niche of Y. pestis differs between its native and invaded regions. The Asian niche overpredicted the distribution of Y. pestis across North America. Including biotic factors along with the native climatic niche increased niche overlap between the native and invaded models, and models containing only biotic factors performed better than the native climatic niche alone. Geographical null models confirmed that the increased niche overlap through inclusion of biotic factors did not, with a couple of exceptions, arise solely from spatially autocorrelated occurrences. Main conclusions The current climatic niche in Central Asia differs from the current climatic niche in North America. Inclusion of biotic factors improved the fit of models to the Y. pestis distribution data in its invaded region better than climate variables alone. This highlights the importance of host species when investigating zoonotic disease introductions and suggests that climatic variables alone are insufficient to predict disease distribution in novel environments.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Increasing picocyanobacteria success in shelf waters contributes to long‐term food web degradation - Katrin Schmidt; Antony J. Birchill; Angus Atkinson; Robert J. W. Brewin; James R. Clark; Anna E. Hickman; David G. Johns; Maeve C. Lohan; Angela Milne; Silvia Pardo; Luca Polimene; Tim J. Smyth; et al. (Global Change Biology, 2020)
Continental margins are disproportionally important for global primary production, fisheries and CO 2 uptake. However, across the Northeast Atlantic shelves, there has been an ongoing summertime decline of key biota—large diatoms, dinoflagellates and copepods—that traditionally fuel higher tropic levels such as fish, sea birds and marine mammals. Here, we combine multiple time series with in situ process studies to link these declines to summer nutrient stress and increasing proportions of picophytoplankton that can comprise up to 90% of the combined pico‐ and nanophytoplankton biomass in coastal areas. Among the pico‐fraction, it is the cyanobacterium Synechococcus that flourishes when iron and nitrogen resupply to surface waters are diminished. Our field data show how traits beyond small size give Synechococcus a competitive edge over pico‐ and nanoeukaryotes. Key is their ability to grow at low irradiances near the nutricline, which is aided by their superior light‐harvesting system and high affinity to iron. However, minute size and lack of essential biomolecules (e.g. omega‐3 polyunsaturated fatty acids and sterols) render Synechococcus poor primary producers to sustain shelf sea food webs efficiently. The combination of earlier spring blooms and lower summer food quantity and quality creates an increasing period of suboptimal feeding conditions for zooplankton at a time of year when their metabolic demand is highest. We suggest that this nutrition‐related mismatch has contributed to the widespread, ~50% decline in summer copepod abundance we observe over the last 60 years. With Synechococcus clades being prominent from the tropics to the Arctic and their abundances increasing worldwide, our study informs projections of future food web dynamics in coastal and shelf areas where droughts and stratification lead to increasing nutrient starvation of surface waters.

Evolutionary history drives aspects of stoichiometric niche variation and functional effects within a guild - Carla L. Atkinson; Brian C. van Ee; John M. Pfeiffer (Ecology, 2020)
Functional traits are characteristics of an organism that represents how it interacts with its environment and can influence the structure and function of ecosystems. Ecological stoichiometry provides a framework to understand ecosystem structure and function by modeling the coupled flow of elements (e.g. carbon [C], nitrogen [N], phosphorus [P]) between consumers and their environment. Animals tend to be homeostatic in their nutrient requirements and preferentially sequester the element in shortest supply relative to demand, and release relatively more of the element in excess. Tissue stoichiometry is an important functional trait that allows for predictions among the elemental composition of animals, their diet, and their waste products, with important effects on the cycling and availability of nutrients in ecosystems. Here, we examined the tissue stoichiometric niches (C:N:P) and nutrient recycling stoichiometries (N:P) of several filter‐feeding freshwater mussels in the subfamily Ambleminae. Despite occupying the same functional‐feeding group and being restricted to a single subfamily‐level radiation, we found that species occupied distinct stoichiometric niches and that these niches varied, in part, as a function of their evolutionary history. The relationship between phylogenetic divergence and functional divergence suggests that evolutionary processes may be shaping niche complementarity and resource partitioning. Tissue and excretion stoichiometry were negatively correlated as predicted by stoichiometric theory. When scaled to the community, higher species richness and phylogenetic diversity resulted in greater functional evenness and reduced functional dispersion. Filter‐feeding bivalves are an ecologically important guild in freshwater ecosystems globally, and our study provides a more nuanced view of the stoichiometric niches and ecological functions performed by this phylogenetically and ecologically diverse assemblage.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Long-Term Change of Demersal Fish Assemblages on the Inshore Agulhas Bank Between 1904 and 2015 - Jock C. Currie; Lara J. Atkinson; Kerry J. Sink; Colin G. Attwood (Frontiers in Marine Science, 2020)

Renewable energy development threatens many globally important biodiversity areas - Jose A. Rehbein; James E. M. Watson; Joe L. Lane; Laura J. Sonter; Oscar Venter; Scott C. Atkinson; James R. Allan (Global Change Biology, 2020)
Transitioning from fossil fuels to renewable energy is fundamental for halting anthropogenic climate change. However, renewable energy facilities can be land‐use intensive and impact conservation areas, and little attention has been given to whether the aggregated effect of energy transitions poses a substantial threat to global biodiversity. Here, we assess the extent of current and likely future renewable energy infrastructure associated with onshore wind, hydropower and solar photovoltaic generation, within three important conservation areas: protected areas (PAs), Key Biodiversity Areas (KBAs) and Earth's remaining wilderness. We identified 2,206 fully operational renewable energy facilities within the boundaries of these conservation areas, with another 922 facilities under development. Combined, these facilities span and are degrading 886 PAs, 749 KBAs and 40 distinct wilderness areas. Two trends are particularly concerning. First, while the majority of historical overlap occurs in Western Europe, the renewable electricity facilities under development increasingly overlap with conservation areas in Southeast Asia, a globally important region for biodiversity. Second, this next wave of renewable energy infrastructure represents a ~30% increase in the number of PAs and KBAs impacted and could increase the number of compromised wilderness areas by ~60%. If the world continues to rapidly transition towards renewable energy these areas will face increasing pressure to allow infrastructure expansion. Coordinated planning of renewable energy expansion and biodiversity conservation is essential to avoid conflicts that compromise their respective objectives.

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Dose evaluation of intravenous metamizole (dipyrone) in infants and children: a prospective population pharmacokinetic study - Victoria C. Ziesenitz; Frédérique Rodieux; Andrew Atkinson; Carole Borter; Julia A. Bielicki; Manuel Haschke; Urs Duthaler; Fabio Bachmann; Thomas O. Erb; Nicolas Gürtler; Stefan Holland-Cunz; Johannes N. van den Anker; et al. (European Journal of Clinical Pharmacology, 2019)

Nutrient recycling by insect and fish communities in high-elevation tropical streams - Carla L. Atkinson; Alexander V. Alexiades; Keeley L. MacNeill; Andrea C. Encalada; Steve A. Thomas; Alexander S. Flecker (Hydrobiologia, 2019)

Diet of northern sea otters ( Enhydra lutris kenyoni ) from Icy Strait, Alaska, based on stomach contents analysis - Kristin L. Brown; Shannon Atkinson; Kierstin B. Keller; Heidi C. Pearson (Marine Mammal Science, 2019)

Biomass distribution of fishes and mussels mediates spatial and temporal heterogeneity in nutrient cycling in streams - Garrett W. Hopper; Keith B. Gido; Caryn C. Vaughn; Thomas B. Parr; Traci G. Popejoy; Carla L. Atkinson; Kiza K. Gates (Oecologia, 2018)

Oust the louse: leaping behaviour removes sea lice from wild juvenile sockeye salmon Oncorhynchus nerka - Emma M. Atkinson; Andrew W. Bateman; Lawrence M. Dill; Martin Krkošek; John D. Reynolds; Sean C. Godwin (Journal of Fish Biology, 2018)
We conducted a manipulative field experiment to determine whether the leaping behaviour of wild juvenile sockeye salmon Oncorhynchus nerka dislodges ectoparasitic sea lice Caligus clemensi and Lepeophtheirus salmonis by comparing sea‐lice abundances between O. nerka juveniles prevented from leaping and juveniles allowed to leap at a natural frequency. Juvenile O. nerka allowed to leap had consistently fewer sea lice after the experiment than fish that were prevented from leaping. Combined with past research, these results imply potential costs due to parasitism and indicate that the leaping behaviour of juvenile O. nerka does, in fact, dislodge sea lice.

Determinants of food resource assimilation by stream insects along a tropical elevation gradient - Carla L. Atkinson; Andrea C. Encalada; Amanda T. Rugenski; Steve A. Thomas; Andrea Landeira-Dabarca; N. LeRoy Poff; Alexander S. Flecker (Oecologia, 2018)

Consumer Aggregations Drive Nutrient Dynamics and Ecosystem Metabolism in Nutrient-Limited Systems - Carla L. Atkinson; Brandon J. Sansom; Caryn C. Vaughn; Kenneth J. Forshay (Ecosystems, 2018)

Long-term change in epibenthic assemblages at the Prince Edward Islands: a comparison between 1988 and 2013 - C. E. O. von der Meden; L. J. Atkinson; G. M. Branch; S. Asdar; I. J. Ansorge; M. van den Berg (Polar Biology, 2017)

The potential role of Antarctic krill faecal pellets in efficient carbon export at the marginal ice zone of the South Orkney Islands in spring - A. Belcher; G. A. Tarling; C. Manno; A. Atkinson; P. Ward; G. Skaret; S. Fielding; S. A. Henson; R. Sanders (Polar Biology, 2017)

Potential cardiovascular adverse events when phenylephrine is combined with paracetamol: simulation and narrative review - Hartley C. Atkinson; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Erratum to: Increased bioavailability of phenylephrine by co-administration of acetaminophen: results of four open-label, crossover pharmacokinetic trials in healthy volunteers - Hartley C. Atkinson; Ioana Stanescu; Isam I. Salem; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Combination paracetamol and ibuprofen for pain relief after oral surgery: a dose ranging study - Hartley C. Atkinson; John Currie; John Moodie; Simon Carson; Steven Evans; James P. Worthington; Leon J. Steenberg; Eileen Bisley; Chris Frampton (European Journal of Clinical Pharmacology, 2015)

Influence of nocturnal and daytime sleep on initial orthostatic hypotension - N. C. S. Lewis; H. Jones; P. N. Ainslie; A. Thompson; K. Marrin; G. Atkinson (European Journal of Applied Physiology, 2015)

Increased bioavailability of phenylephrine by co-administration of acetaminophen: results of four open-label, crossover pharmacokinetic trials in healthy volunteers - Hartley C. Atkinson; Ioana Stanescu; Isam I. Salem; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Captive rearing for Chinook salmon (Oncorhynchus tshawytscha) and Atlantic salmon (Salmo salar): the Idaho and Maine experiences - Eric J. Stark; Ernest J. Atkinson; Christine C. Kozfkay (Reviews in Fish Biology and Fisheries, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Exploring the spatio-temporal relationship between two key aeroallergens and meteorological variables in the United Kingdom - Nabaz Khwarahm; Jadunandan Dash; Peter M. Atkinson; R. M. Newnham; C. A. Skjøth; B. Adams-Groom; Eric Caulton; K. Head (International Journal of Biometeorology, 2014)

Tracing Consumer-Derived Nitrogen in Riverine Food Webs - Carla L. Atkinson; Jeffrey F. Kelly; Caryn C. Vaughn (Ecosystems, 2014)

Erratum to: Dissolved inorganic carbon and total alkalinity of a Hawaiian fringing reef: chemical techniques for monitoring the effects of ocean acidification on coral reefs - C. A. Lantz; M. J. Atkinson; C. W. Winn; S. E. Kahng (Coral Reefs, 2014)

Dissolved inorganic carbon and total alkalinity of a Hawaiian fringing reef: chemical techniques for monitoring the effects of ocean acidification on coral reefs - C. A. Lantz; M. J. Atkinson; C. W. Winn; S. E. Kahng (Coral Reefs, 2014)

Feeding and overwintering of Antarctic krill across its major habitats: The role of sea ice cover, water depth, and phytoplankton abundance - Katrin Schmidt; Angus Atkinson; David W. Pond; Louise C. Ireland (Limnology and Oceanography, 2014)
Antarctic krill ( Euphausia superba ) were sampled in contrasting habitats: a seasonally ice‐covered deep ocean (Lazarev Sea), ice‐free shelves at their northern range (South Georgia) and the Antarctic Peninsula (Bransfield Strait), and shelf and oceanic sites in the Scotia Sea. Across 92 stations, representing a year‐round average, the food volume in krill stomachs comprised 71 ± 29% algae, 17 ± 21% protozoans, and 12 ± 25% metazoans. Fatty acid trophic markers showed that copepods were consistently part of krill diet, not a switch food. In open waters, both diatom and copepod consumption increased with phytoplankton abundance. Under sea ice, ingestion of diatoms became rare, whereas feeding on copepods remained constant. During winter, larvae contained high but variable proportions of diatom markers, whereas in postlarvae the role of copepods increased with krill body length. Overwintering differed according to habitat. Krill from South Georgia had lower lipid stores than those from the Bransfield Strait or Lazarev Sea. Feeding effort was much reduced in Lazarev Sea krill, whereas most individuals from the Bransfield Strait and South Georgia contained phytoplankton and seabed detritus in their stomachs. Their retention of essential body reserves indicates that krill experienced most winter hardship in the Lazarev Sea, followed by South Georgia and then Bransfield Strait. This was reflected in the delayed development from juveniles to adults in the Lazarev Sea. Circumpolar comparisons of length frequencies suggest that krill growth conditions are more favorable in the southwest Atlantic than in the Lazarev Sea or off East Antarctica because of longer phytoplankton bloom periods and rewarding access to benthic food.

An intra-specific linkage map of lettuce (Lactuca sativa) and genetic analysis of postharvest discolouration traits - Laura D. Atkinson; Leah K. McHale; María José Truco; Howard W. Hilton; James Lynn; Johan W. Schut; Richard W. Michelmore; Paul Hand; David A. C. Pink (Theoretical and Applied Genetics, 2013)

Nematode 18S rRNA gene is a reliable tool for environmental biosafety assessment of transgenic banana in confined field trials - R. Nakacwa; A. Kiggundu; H. Talwana; J. Namaganda; C. Lilley; W. Tushemereirwe; H. Atkinson (Transgenic Research, 2013)

Cooperation between scientists, NGOs and industry in support of sustainable fisheries: the South African hake Merluccius spp. trawl fishery experience a - J. G. Field; C. G. Attwood; A. Jarre; K. Sink; L. J. Atkinson; S. Petersen (Journal of Fish Biology, 2013)
This paper examines the increasingly close interaction between natural and social scientists, non‐governmental organizations (NGO) and industry, in pursuit of responsible ecosystem‐based management of fisheries. South Africa has committed to implementing an ecosystem approach to fisheries management. Management advice stems from multi‐stakeholder representation on government‐led scientific and management working groups. In the hake Merluccius capensis and Merluccius paradoxus fishery, the primary management measure is an annual total allowable catch ( TAC ), the level of which is calculated using a management procedure ( MP ) that is revised approximately every 4 years. Revision of the MP is a consultative process involving most stakeholders, and is based on simulation modelling of projected probable scenarios of resource and fishery dynamics under various management options. NGOs , such as the Worldwide Fund for Nature in South Africa (WWF‐SA), have played an important role in influencing consumers, the fishing industry and government to develop responsible fishing practices that minimize damage to marine ecosystems. Cooperation between industry, government and scientists has helped to improve sustainability and facilitated the meeting of market‐based incentives for more responsible fisheries. Research includes ecosystem modelling, spatial analysis and ecosystem risk assessment with increasing research focus on social and economic aspects of the fishery. A four‐year cooperative experiment to quantify the effect of trawling on benthic community structure is being planned. The food requirements of top predators still need to be included in the TAC ‐setting formulae and more social and economic research is needed. This paper also demonstrates how NGO initiatives such as Marine Stewardship Council certification and the Southern African Sustainable Seafood Initiative, a traffic light system of classifying seafood for consumers, have contributed to responsible fishing practices, increased ecosystem research and public awareness. This fishery appears to have a good future, provided that the monitoring, control and surveillance systems continue to function, TACs remain within ecologically sustainable limits and the effective collaboration between government, industry, scientists and NGOs continues to drive positive change.

Aggregated filter‐feeding consumers alter nutrient limitation: consequences for ecosystem and community dynamics - Carla L. Atkinson; Caryn C. Vaughn; Kenneth J. Forshay; Joshua T. Cooper (Ecology, 2013)
Nutrient cycling is a key process linking organisms in ecosystems. This is especially apparent in stream environments in which nutrients are taken up readily and cycled through the system in a downstream trajectory. Ecological stoichiometry predicts that biogeochemical cycles of different elements are interdependent because the organisms that drive these cycles require fixed ratios of nutrients. There is growing recognition that animals play an important role in biogeochemical cycling across ecosystems. In particular, dense aggregations of consumers can create biogeochemical hotspots in aquatic ecosystems via nutrient translocation. We predicted that filter‐feeding freshwater mussels, which occur as speciose, high‐biomass aggregates, would create biogeochemical hotspots in streams by altering nutrient limitation and algal dynamics. In a field study, we manipulated nitrogen and phosphorus using nutrient‐diffusing substrates in areas with high and low mussel abundance, recorded algal growth and community composition, and determined in situ mussel excretion stoichiometry at 18 sites in three rivers (Kiamichi, Little, and Mountain Fork Rivers, south‐central United States). Our results indicate that mussels greatly influence ecosystem processes by modifying the nutrients that limit primary productivity. Sites without mussels were N‐limited with ∼26% higher relative abundances of N‐fixing blue‐green algae, while sites with high mussel densities were co‐limited (N and P) and dominated by diatoms. These results corroborated the results of our excretion experiments; our path analysis indicated that mussel excretion has a strong influence on stream water column N:P. Due to the high N:P of mussel excretion, strict N‐limitation was alleviated, and the system switched to being co‐limited by both N and P. This shows that translocation of nutrients by mussel aggregations is important to nutrient dynamics and algal species composition in these rivers. Our study highlights the importance of consumers and this imperiled faunal group on nutrient cycling and community dynamics in aquatic ecosystems.

Structural, kinetic and computational investigation of Vitis vinifera DHDPS reveals new insight into the mechanism of lysine-mediated allosteric inhibition - Sarah C. Atkinson; Con Dogovski; Matthew T. Downton; Peter E. Czabotar; Renwick C. J. Dobson; Juliet A. Gerrard; John Wagner; Matthew A. Perugini (Plant Molecular Biology, 2013)

Influence of Tyrphostin AG490 on the expression of diabetes-associated markers in human adipocytes - Abdoreza Davoodi-Semiromi; C. H. Wasserfall; A. Hassanzadeh; R. M. Cooper-DeHoff; M. Wabitsch; M. Atkinson (Immunogenetics, 2013)

Recombinant monoclonal antibody yield in transgenic tobacco plants is affected by the wounding response via an ethylene dependent mechanism - Sally Hassan; Richard Colgan; Mathew J. Paul; Christopher J. Atkinson; Amy L. Sexton; Craig J. van Dolleweerd; Eli Keshavarz-Moore; Julian K-C. Ma (Transgenic Research, 2012)

Species distribution modeling of storm-petrels (Oceanodroma furcata and O. leucorhoa) in the North Pacific and the role of dimethyl sulfide - G. R. W. Humphries; F. Huettmann; G. A. Nevitt; C. Deal; D. Atkinson (Polar Biology, 2012)

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Diurnal variation in the salivary melatonin responses to exercise: relation to exercise-mediated tachycardia - K. Marrin; B. Drust; W. Gregson; C. J. Morris; N. Chester; G. Atkinson (European Journal of Applied Physiology, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate - P. Cuet; M. J. Atkinson; J. Blanchot; B. E. Casareto; E. Cordier; J. Falter; P. Frouin; H. Fujimura; C. Pierret; Y. Susuki; C. Tourrand (Coral Reefs, 2011)

Water velocity dependence of phosphate uptake on a coral-dominated fringing reef flat, La Réunion Island, Indian Ocean - P. Cuet; C. Pierret; E. Cordier; M. J. Atkinson (Coral Reefs, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Mobility properties of the Hermes transposable element in transgenic lines of Aedes aegypti - Ryan C. Smith; Peter W. Atkinson (Genetica, 2011)

Mapping the phenology of natural vegetation in India using a remote sensing-derived chlorophyll index - C. Jeganathan; J. Dash; P. M. Atkinson (International Journal of Remote Sensing, 2010)

Cadmium, Copper, Iron, and Zinc Concentrations in Kidneys of Grey Wolves, Canis lupus, from Alaska, Idaho, Montana (USA) and the Northwest Territories (Canada) - S. R. Hoffmann; S. A. Blunck; K. N. Petersen; E. M. Jones; J. C. Koval; R. Misek; J. A. Frick; H. D. Cluff; C. A. Sime; M. McNay; K. B. Beckman; M. W. Atkinson; et al. (Bulletin of Environmental Contamination and Toxicology, 2010)

On the seasonal cycles and variability of Florida Straits, Ekman and Sverdrup transports at 26° N in the Atlantic Ocean - C. P. Atkinson; H. L. Bryden; J. J-M. Hirschi; T. Kanzow (Ocean Science, 2010)
Since April 2004 the RAPID array has made continuous measurements of the Atlantic Meridional Overturning Circulation (AMOC) at 26° N. Two key components of this system are Ekman transport zonally integrated across 26° N and western boundary current transport in the Florida Straits. Whilst measurements of the AMOC as a whole are somewhat in their infancy, this study investigates what useful information can be extracted on the variability of the Ekman and Florida Straits transports using the decadal timeseries already available. Analysis is also presented for Sverdrup transports zonally integrated across 26° N. The seasonal cycles of Florida Straits, Ekman and Sverdrup transports are quantified at 26° N using harmonic analysis of annual and semi-annual constituents. Whilst Sverdrup transport shows clear semi-annual periodicity, calculations of seasonal Florida Straits and Ekman transports show substantial interannual variability due to contamination by variability at non-seasonal frequencies; the mean seasonal cycle for these transports only emerges from decadal length observations. The Florida Straits and Ekman mean seasonal cycles project on the AMOC with a combined peak-to-peak seasonal range of 3.5 Sv. The combined seasonal range for heat transport is 0.40 PW. The Florida Straits seasonal cycle possesses a smooth annual periodicity in contrast with previous studies suggesting a more asymmetric structure. No clear evidence is found to support significant changes in the Florida Straits seasonal cycle at sub-decadal periods. Whilst evidence of wind driven Florida Straits transport variability is seen at sub-seasonal and annual periods, a model run from the 1/4° eddy-permitting ocean model NEMO is used to identify an important contribution from internal oceanic variability at sub-annual and interannual periods. The Ekman transport seasonal cycle possesses less symmetric structure, due in part to different seasonal transport regimes east and west of 50 to 60° W. Around 60% of non-seasonal Ekman transport variability occurs in phase section-wide at 26° N and is related to the NAO, whilst Sverdrup transport variability is more difficult to decompose.

Effects of alcohol preload on attentional bias towards cocaine-related cues - Catharine Montgomery; Matt Field; Amanda M. Atkinson; Jon C. Cole; Andrew J. Goudie; Harry R. Sumnall (Psychopharmacology, 2010)

The Challenges of Dewatering at the Victor Diamond Mine in Northern Ontario, Canada - L. C. Atkinson; P. G. Keeping; J. C. Wright; Houmao Liu (Mine Water and the Environment, 2010)

Applying the HAZUS-MH software tool to assess seismic risk in downtown Ottawa, Canada - S. K. Ploeger; G. M. Atkinson; C. Samson (Natural Hazards, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

Associations between endogenous sex hormone levels and mammographic and bone densities in premenopausal women - Mellissa Yong; Charlotte Atkinson; Katherine M. Newton; Erin J. Aiello Bowles; Frank Z. Stanczyk; Kim C. Westerlind; Victoria L. Holt; Stephen M. Schwartz; Wendy M. Leisenring; Johanna W. Lampe (Cancer Causes & Control, 2009)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Daidzein-metabolizing phenotypes in relation to serum hormones and sex hormone binding globulin, and urinary estrogen metabolites in premenopausal women in the United States - Charlotte Atkinson; Katherine M. Newton; Frank Z. Stanczyk; Kim C. Westerlind; Lin Li; Johanna W. Lampe (Cancer Causes & Control, 2008)

Occurrence and Distribution of Polycyclic Aromatic Hydrocarbons (PAHs) in Bolgoda and Beira Lakes, Sri Lanka - K. A. S. Pathiratne; O. C. P. De Silva; David Hehemann; Ian Atkinson; Robert Wei (Bulletin of Environmental Contamination and Toxicology, 2007)

Idiopathic muscle necrosis in the Norway lobster, Nephrops norvegicus (L.): aetiology, pathology and progression to bacteraemia - I D Ridgway; G D Stentiford; A C Taylor; R J A Atkinson; T H Birkbeck; D M Neil (Journal of Fish Diseases, 2007)
The pathology and progression of idiopathic muscle necrosis (IMN) in Nephrops norvegicus and possible aetiologies have been investigated. Trawl capture, aerial exposure and handling initiate IMN, and the condition can be induced through periods of aerial exposure alone, in the absence of trawling. Within 24–48 h after trawl capture IMN progresses to a multi‐species bacterial septicaemia, with moribund animals exhibiting clinical signs. The aetiology of this condition has been examined using molecular (16S rRNA gene sequencing) and biochemical (standard taxonomic assays, Biolog TM ) criteria to characterize bacterial isolates from moribund and healthy animals. Histopathology of the IMN phase reveals a loss of sarcomeric structure with necrotic lesions containing pyknotic nuclei, fragments of myofibrils and connective tissue elements. In the bacterial phase there is extensive loss of abdominal muscle structure, and the presence of rod‐shaped Gram‐negative bacteria in the degrading tissues. The results demonstrate that the IMN condition is connected to stressful conditions imposed on N. norvegicus , but involves no pathogenic agents. This is followed by an opportunistic bacterial infection that causes further tissue spoilage. It is believed that the primary cause of both IMN and bacteraemia is imposed stress, but they are expressed in different time courses.

Monitoring the earth. Physical geology in action. C. Vita‐Finzi. Publisher Terra, Harpenden, 2003. 189 pp. ISBN 1‐903544‐12‐2 - T. C. Atkinson (Journal of Quaternary Science, 2006)

Prevalence and differential host‐specificity of two avian blood parasite genera in the Australo‐Papuan region - JON S. BEADELL; EBEN GERING; JEREMY AUSTIN; JOHN P. DUMBACHER; MIKE A. PEIRCE; THANE K. PRATT; CARTER T. ATKINSON; ROBERT C. FLEISCHER (Molecular Ecology, 2004)
The degree to which widespread avian blood parasites in the genera Plasmodium and Haemoproteus pose a threat to novel hosts depends in part on the degree to which they are constrained to a particular host or host family. We examined the host distribution and host‐specificity of these parasites in birds from two relatively understudied and isolated locations: Australia and Papua New Guinea. Using polymerase chain reaction (PCR), we detected infection in 69 of 105 species, representing 44% of individuals surveyed ( n = 428). Across host families, prevalence of Haemoproteus ranged from 13% (Acanthizidae) to 56% (Petroicidae) while prevalence of Plasmodium ranged from 3% (Petroicidae) to 47% (Ptilonorhynchidae). We recovered 78 unique mitochondrial lineages from 155 sequences. Related lineages of Haemoproteus were more likely to derive from the same host family than predicted by chance at shallow (average LogDet genetic distance = 0, n = 12, P = 0.001) and greater depths (average distance = 0.014, n = 11, P Haemoproteus subclades identified in a maximum likelihood phylogeny, host‐specificity was evident up to parasite genetic distances of 0.029 and 0.007 based on logistic regression. We found no significant host relationship among lineages of Plasmodium by any method of analysis. These results support previous evidence of strong host‐family specificity in Haemoproteus and suggest that lineages of Plasmodium are more likely to form evolutionarily–stable associations with novel hosts.

Natural selection of the major histocompatibility complex ( Mhc ) in Hawaiian honeycreepers (Drepanidinae) - SUSAN I. JARVI; CHERYL L. TARR; CARL E. MCINTOSH; CARTER T. ATKINSON; ROBERT C. FLEISCHER (Molecular Ecology, 2004)
The native Hawaiian honeycreepers represent a classic example of adaptive radiation and speciation, but currently face one the highest extinction rates in the world. Although multiple factors have likely influenced the fate of Hawaiian birds, the relatively recent introduction of avian malaria is thought to be a major factor limiting honeycreeper distribution and abundance. We have initiated genetic analyses of class II β chain Mhc genes in four species of honeycreepers using methods that eliminate the possibility of sequencing mosaic variants formed by cloning heteroduplexed polymerase chain reaction products. Phylogenetic analyses group the honeycreeper Mhc sequences into two distinct clusters. Variation within one cluster is high, with d N > d S and levels of diversity similar to other studies of Mhc ( B system) genes in birds. The second cluster is nearly invariant and includes sequences from honeycreepers (Fringillidae), a sparrow (Emberizidae) and a blackbird (Emberizidae). This highly conserved cluster appears reminiscent of the independently segregating Rfp‐Y system of genes defined in chickens. The notion that balancing selection operates at the Mhc in the honeycreepers is supported by transpecies polymorphism and strikingly high d N / d S ratios at codons putatively involved in peptide interaction. Mitochondrial DNA control region sequences were invariant in the i’iwi, but were highly variable in the ‘amakihi. By contrast, levels of variability of class II β chain Mhc sequence codons that are hypothesized to be directly involved in peptide interactions appear comparable between i’iwi and ‘amakihi. In the i’iwi, natural selection may have maintained variation within the Mhc , even in the face of what appears to a genetic bottleneck.

Multitrophic interactions involving genetically modified potatoes, nontarget aphids, natural enemies and hyperparasitoids - S. E. Cowgill; C. Danks; H. J. Atkinson (Molecular Ecology, 2004)
Genetically modified (GM) potatoes expressing a cysteine proteinase inhibitor (cystatin) have been developed as an option for the management of plant parasitic nematodes. The relative impact of such plants on predators and parasitoids (natural enemies) of nontarget insects was determined in a field trial. The trial consisted of GM plants, control plants grown in soil treated with a nematicide and untreated control plants. The quantity of nontarget aphids and their quality as hosts for natural enemies were studied. Aphid density was significantly reduced by nematicide treatment and few natural enemies were recorded from treated potatoes during the study. In contrast, similar numbers of aphids and their more adundant predators were recorded from the untreated control and the GM potatoes. The size of aphids on GM and control plants was recorded twice during the study. During the first sampling period (2–9 July) aphids clip‐caged on GM plants were smaller than those on control plants. During the second sampling period (23–30 July) there was no difference in aphid size between those from the GM and control plants. Host size is an important component of host quality. It can affect the size and fecundity of parasitoid females and the sex ratio of their offspring. However, neither the fitness of females of Aphidius ervi, the most prevalent primary parasitoid, nor the sex ratio of their progeny, were affected when the parasitoids developed on aphids feeding on GM plants. Two guilds of secondary parasitoid were also recorded during the study. The fitness of the most abundant species, Aspahes vulgaris, was not affected when it developed on hosts from GM plants. The transgene product, OC IΔD86, was not detected in aphids that had fed on GM plants in the field, suggesting that there is minimal secondary exposure of natural enemies to the inhibitor. The results indicate that transgenic nematode resistance is potentially more compatible with aphid biological control than is current nematicide use.

Habitat selection in whiting - C. J. L. Atkinson; M. Bergmann; M. J. Kaiser (Journal of Fish Biology, 2004)
Given a choice of habitats in a laboratory experiment, whiting Merlangius merlangus preferentially spent most time over sand, then gravel and least time over a habitat with emergent structures. The introduction of a predator stimulus increased the preference for the sand habitat for large whiting, whereas small whiting had an increased preference for the habitat with emergent structures.

Patterns of Hermes transposition in Drosophila melanogaster - N. Guimond; D. K. Bideshi; A. C. Pinkerton; P. W. Atkinson; D. A. O'Brochta (Molecular Genetics and Genomics, 2003)

Response to the comment by G. Symonds, K.P. Black, and I.R. Young on "A physical derivation of nutrient-uptake rates in coral reefs: effects of roughness and waves - C. Hearn; M. Atkinson; J. Falter (Coral Reefs, 2002)

Transgenic potatoes with enhanced levels of nematode resistance do not have altered susceptibility to nontarget aphids - S. E. Cowgill; C. Wright; H. J. Atkinson (Molecular Ecology, 2002)
Cysteine proteinase inhibitors (cystatins) confer resistance to plant‐parasitic nematodes when expressed in transgenic plants. The survival and growth of nymphs of the peach‐potato aphid, Myzus persicae, were adversely affected when cystatins were added to artificial diets. When aphids were clip‐caged onto transgenic plants expressing chicken egg white cystatin (CEWc) there was no adverse effect on aphid fitness. Field populations of aphids on transgenic Desiree potatoes, expressing CEWc or a modified version of oryzacystatin I, were not significantly different from populations on control Desiree plants. The effect of other nematode management options on aphid numbers was also studied. A conventionally bred cultivar, with partial nematode resistance, supported higher populations of aphids than the transgenic lines at the beginning of the sampling period. Peak aphid densities on the untreated control and untreated transgenic lines were 7 and 5.2 aphids per plant. Aldicarb, commonly used to control nematodes on potatoes, reduced the value to less than 0.2 aphids per plant. The results demonstrate that levels of expression in the plant tissue actually consumed are important in determining the risk of cystatins to nontarget invertebrates. The study also highlights the importance of including currently used management options in any assessment of the impact of transgenic plants on nontarget organisms.

Sucrose Phosphate Synthase Genes in Plants Belong to Three Different Families - Georg Langenkämper; Raymond W.M. Fung; Richard D. Newcomb; Ross G. Atkinson; Richard C. Gardner; Elspeth A. MacRae (Journal of Molecular Evolution, 2002)

Nutrient dynamics in the Biosphere 2 coral reef mesocosm: water velocity controls NH4 and PO4 uptake - M. Atkinson; J. Falter; C. Hearn (Coral Reefs, 2001)

A physical derivation of nutrient-uptake rates in coral reefs: effects of roughness and waves - C. Hearn; M. Atkinson; J. Falter (Coral Reefs, 2001)

MDH1: an apple homeobox gene belonging to the BEL1 family - Yi-Hu Dong; Jia-Long Yao; Ross G. Atkinson; Joanna J. Putterill; Bret A. Morris; Richard C. Gardner (Plant Molecular Biology, 2000)

U-series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

U‐series dating of Hoxnian interglacial deposits at Marks Tey, Essex, England - P. J. Rowe; T. C. Atkinson; C. Turner (Journal of Quaternary Science, 1999)

Evaluation of the Best disease gene in patients with age-related macular degeneration and other maculopathies - R. Allikmets; Johanna M. Seddon; Paul S. Bernstein; A. Hutchinson; Andrew Atkinson; Sanjay Sharma; Bernard Gerrard; W. Li; Michael L. Metzker; Claes Wadelius; C. Thomas Caskey; Michael Dean; et al. (Human Genetics, 1999)

An integrated genetic linkage map of the laboratory rat - Donna M. Brown *, , Tara C. Matise; George Koike; Jason S. Simon; Eric S. Winer; Sarah Zangen; Michael G. McLaughlin; Masahide Shiozawa; O. Scott Atkinson; James R. Hudson, Jr.; Aravinda Chakravarti; Eric S. Lander **, , Howard (Mammalian Genome, 1998)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Expression of an engineered cysteine proteinase inhibitor (Oryzacystatin-IΔD86) for nematode resistance in transgenic rice plants - P. Vain; B. Worland; M. C. Clarke; G. Richard; M. Beavis; H. Liu; A. Kohli; M. Leech; J. Snape; P. Christou; H. Atkinson (Theoretical and Applied Genetics, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Observations on the Burrows and Burrowing Behaviour of: Squilla mantis L. Crustacea: Stomatopoda - R. J. A. ATKINSON; C. FROGLIA; E. ARNERI; B. ANTOLINI (Marine Ecology, 1997)
The burrows of Squilla mantis are described from polyester resin casts taken at two Adriatic sites near Ancona. Typically, burrows had two openings, one of which was larger than the other, and were basically U‐shaped. An interesting association with the little‐known caridean shrimp Athanas amazone was observed. The sediments occupied by S. mantis were silty sands and sandy muds. Field observations of S. mantis and other species on the same grounds are presented and some information on burrow density is given, derived from burrow counts using underwater television. Burrowing behaviour is described from observations of animals transferred to laboratory aquaria.

Filtration enhances suspended sediment deposition from surface water to granular permeable beds - David C J. D. Royal; Marcus I. Bursik; Joseph F. Atkinson; Joseph V. Depinto (Water, Air, & Soil Pollution, 1997)

A LARGE PLACENTA ENCOUNTERED IN THE HAWAIIAN WINTER GROUNDS OF THE HUMPBACK WHALE, MEGAPTERA NOVAEANGLIAE - L. E. Silvers; S. Atkinson; M. Iwasa; C. Combelles; D. R. Salden (Marine Mammal Science, 1997)

Biochemical composition of Nephrops norvegicus : changes associated with ovary maturation - I. D. Tuck; A. C. Taylor; R. J. A. Atkinson; M. E. Gramitto; C. Smith (Marine Biology, 1997)

The allopolyploid origin of kiwifruit,Actinidia deliciosa (Actinidiaceae) - Ross G. Atkinson; Guido Cipriani; David J. Whittaker; Richard C. Gardner (Plant Systematics and Evolution, 1997)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

A study of the atmospheric reactions of 1,3-dichloropropene and other selected organochlorine compounds - Ernesto C. Tuazon; Roger Atkinson; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1984)